2020
DOI: 10.1136/jitc-2020-001499
|View full text |Cite
|
Sign up to set email alerts
|

RECIST and iRECIST criteria for the evaluation of nivolumab plus ipilimumab in patients with microsatellite instability-high/mismatch repair-deficient metastatic colorectal cancer: the GERCOR NIPICOL phase II study

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) are highly effective in patients with microsatellite instability/mismatch repair-deficient (MSI/dMMR) metastatic colorectal cancer (mCRC). Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 criteria may underestimate response to ICIs due to the pseudoprogression phenomenon. The GERCOR NIPICOL phase II study aimed to evaluate the frequency of pseudoprogressions in patients with MSI/dMMR mCRC treated with nivolumab and ipilimumab.MethodsPatients with MSI/dMMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 34 publications
(28 reference statements)
4
32
0
1
Order By: Relevance
“…In a phase II study of 57 patients with MSI/dMMR mCRC treated with nivolumab and ipilimumab, only 3.5% (2/57) patients experienced PSPD. This result is consistent with the previous study ( 42 ). Parseghian et al.…”
Section: Immune Checkpoint Inhibitors Therapysupporting
confidence: 94%
See 1 more Smart Citation
“…In a phase II study of 57 patients with MSI/dMMR mCRC treated with nivolumab and ipilimumab, only 3.5% (2/57) patients experienced PSPD. This result is consistent with the previous study ( 42 ). Parseghian et al.…”
Section: Immune Checkpoint Inhibitors Therapysupporting
confidence: 94%
“…In a phase II study of 57 patients with MSI/dMMR mCRC treated with nivolumab and ipilimumab, only 3.5% (2/57) patients experienced PSPD. This result is consistent with the previous study (42). Parseghian et al found that PSPD was not seen in 59 MSS mCRC treated with immunotherapy, which may be related to its poor efficacy (29).There are many other mechanisms of drug resistance in tumors.…”
Section: Msi/dmmr Mcrcsupporting
confidence: 91%
“…In this cohort, MMR deficiency was a significant predictor of ORR. In a phase II study that observed the effects of nivolumab plus ipilimumab in patients with MSI-H or MMR-deficient metastatic colorectal cancer, including 56% with LS-related cancers, Cohen et al found that the 12-month progression-free survival (PFS) and overall survival (OS) were 76.5% and 84%, respectively (15). Combined ICI therapy resulted in impressive outcomes in disease control.…”
Section: Commentmentioning
confidence: 99%
“…Like in the latter study, the 6-month and 1-year PFS rates were 75% and 71%. A total of 56% of the patients experienced grade 3–4 AEs [ 19 ]. Dostarlimab, another monoclonal antibody targeting PD-1, showed strong and durable antitumor activity in patients with dMMR gastrointestinal tumors in the phase 1/2b GARNET study.…”
Section: Immune Checkpoint Inhibitors In Msi/dmmr Mcrcmentioning
confidence: 99%
“…Importantly, immediate disease progression was observed in 29.4% of patients treated with pembrolizumab versus 12.3% with chemotherapy. Misdiagnosis of MSI/dMMR status and pseudoprogression phenomenon (pseudoprogression represents up to 50% of patients with immediate disease progression [ 27 ]) might partly explain this observation [ 19 , 27 , 28 , 29 ]. Grade 3 or higher treatment-related adverse events were 21.6% versus 65.7%, including death in one patient receiving chemotherapy.…”
Section: Immune Checkpoint Inhibitors In Msi/dmmr Mcrcmentioning
confidence: 99%